THE EFFECT OF FINANCIAL PERFORMANCE ON THE LEVEL OF FINANCIAL INDEPENDENCE REGIONAL PUBLIC SERVICE AGENCY (BLUD) REGIONAL PUBLIC HOSPITAL (RSUD) INDRASARI RENGAT - Heriasman Heriasman; Walmi Sholihat; Astarman Astarman; Fitri Khairida (LPPM Press STIE Indragiri Rengat, 2022)
The financial performance of the Regional Public Service Agency (BLUD) of RSUD Indrasari Rengat has fluctuated, this greatly affects the level of financial independence as a hospital that has implemented the pattern of financial management of the Regional Public Service Agency (PPK-BLUD). Since 2016-2020, the financial performance of the Indrasari Rengat Hospital for the liquidity ratio seen from the current ratio has decreased. Furthermore, there was an increase in the solvency ratio and fluctuations in the profitability ratio, this was also supported by the research gap of several previous studies such as the research of Wijayanti (2015), Mentari (2018) and Tama (2018). This research was conducted at the BLUD RSUD Indrasari Rengat, the research was carried out for approximately 6 (six) months. The purpose of this study was to analyze and examine the effect of financial performance (Liquidity Ratio - Current Ratio, Solvency Ratio, Profitability Ratio) on the level of financial independence of the BLUD RSUD Indrasari Rengat, Indragiri Hulu Regency. This study uses quantitative methods, namely research that analyzes and examines the effect of financial performance (Liquidity Ratio - Current Ratio, Solvency Ratio, Profitability Ratio) on the level of financial independence of BLUD Indrasari Rengat Hospital, Indragiri Hulu Regency. By analyzing the data using multiple linear regression, correlation coefficient, and hypothesis testing which will later be assisted by using SPSS version 24. Based on the results of the study, it showed that financial performance, namely the liquidity ratio (current ratio), solvency ratio, and profitability ratios had a positive and significant effect on the level of financial independence at the BLUD RSUD Indrasari Rengat.